COMPARISON BETWEEN MICROSCOPY AND RAPID DIAGNOSTIC TESTS IN DIAGNOSIS OF MALARIA AT A TERTIARY CARE MEDICAL INSTITUTION IN UTTARAKHAND (A 3-YEAR STUDY) - Gupta, Pratima; Gupta, Priyanka; Rao, Shalinee; Singh, Neha; Kalita, Deepjyoti (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objectives: Malaria is one of the most prevalent parasitic diseases all over the world including India. Although the microscopic study of stained peripheral blood smear (PBS) is a gold standard of malaria diagnosis due to some subjective errors, rapid diagnostic tests (RDTs) can be a suitable alternative. This study was conducted to estimate the prevalence and demographic details of malaria cases along with a comparison between the two most common screening methods: PBS and RDTs. Methods: Demographic profile, the prevalence of malaria in this region of Uttarakhand and evaluation of efficacy of RDT as a screening method was performed. Analysis of PBS microscopy for malaria parasites was performed and compared with immunochromatography based RDT over a duration of 3 years. Results: Out of total 2982 clinically suspected patients of malaria, 132 were found to be positive by either of the two methods. Prevalence of malaria was 4.4% in our study. Plasmodium vivax was the predominant species isolated (95%). Males outnumbered females with a ratio of 2.1:1. The most common age group affected was 30â€“49 years. Sensitivity and specificity of RDT was found to be 91.8% and 93.8%, respectively. Positive predictive value and negative predictive value were found to be 97.8% and 98.9%, respectively. Conclusion: We conclude that Uttarakhand is a low prevalence area for Malaria and the RDT based on malaria antigen (whole blood) method is as specific and sensitive as the traditional PBS microscopy. Thus, it can be used as an alternative to PBS microscopy.